Research on Detection and Positioning Technology of UHV GIS Based on Multi-Sensor Fusion and Chaotic Cuckoo Algorithm - Zhang, Yongyun; Wang, Jianmin; Chen, Xiaoyu (Informatica, 2025)
Uhv gas-insulated switchgear (GIS) plays an important role in power system, but its UHF partial discharge may cause equipment failure and threaten the safe and stable operation of power system. In this paper, a multi-sensor fusion based UHV GIS UHF local discharge detection and positioning technology is studied. The technology uses multiple sensors to collect the relevant data of UHV GIS equipment, and then through data fusion and analysis, complete the positioning solution under the mixed-team cuckoo algorithm, obtain the accurate location of the local amplifier, and realize the detection and positioning of the UHF local amplifier. In order to test the feasibility of this technology, a case application is also carried out at the end. The result shows that in the UHF test, the signal collected by sensor B is about 7ns ahead of sensor C, and the difference of signal transmission distance is 2.1m, which is consistent with the sensor layout spacing. The signal source is judged to be located on the left side of sensor B. The signal collected by sensor A is about 5ns lower than that of sensor B. It can be determined that the high-frequency signal source is between sensor A and sensor B. At the same time, the coordinate of the local release source is (0.52, 0.12, 0.45), which is the support insulator in the GIS. The abnormal signal is determined to be C-phase internal insulation discharge of T0511 tool brake. The results show that multi-sensor fusion is feasible in GIS location detection, which can effectively prevent equipment failure and improve the reliability of power system.